Terminológiai alapfogalmak régészeti korú üvegtárgyak elemzéséhez - Dévai, Kata (Dissertationes Archaeologicae, 2013)
This study aims at creating a Hungarian glossary of terms, which the Hungarian archaeological publications are short of. To describe the glass objects accurately an all-embracing terminology must be used. Forms of the objects do not provide enough information to their analysis, hence their process of manufacture, the parts of the vessels, the decoration methods, the analysis of the colours and qualities are essential features. The current names of the process, tools and equipment used in modern glass production should be compared with the ones used in ancient times and terms which reflect the ancient methods and devices should be preferred. As some of the ancient manufacture techniques did not have Hungarian name, foreign expressions were applied. In the first part of the article the most frequent equipment and devices are listed. In the second part the principal constituents and the additives of glassmaking are discussed. The third part is an outline of the main glassmaking process. These parts also contribute to the depiction of the objects. The fourth part includes decorating techniques, the fith and the sixth sections deal with the variety of colours and the transparency of objects. The last part represents the characteristic features of glass vessels including the methods of finishing the rims, bases and handles, which were formed at different temperatures.